Fine‐tuning ethanol oxidation pathway enzymes and cofactor PQQ coordinates the conflict between fitness and acetic acid production by Acetobacter pasteurianus - Gao, Ling (John Wiley and Sons Inc., 2020)

(untitled) (Microb Biotechnol)
The very high concentrations required for industrial production of free acetic acid create toxicity and low pH values, which usually conflict with the host cell growth, leading to a poor productivity. Achieving a balance between cell fitness and product synthesis is the key challenge to improving acetic acid production efficiency in metabolic engineering. Here, we show that the synergistic regulation of alcohol/aldehyde dehydrogenase expression and cofactor PQQ level could not only efficiently relieve conflict between increased acetic acid production and compromised cell fitness, but also greatly enhance acetic acid tolerance of Acetobacter pasteurianus to a high initial concentration (3% v/v) of acetic acid. Combinatorial expression of adhA and pqqABCDE greatly shortens the duration of starting‐up process from 116 to 99 h, leading to a yield of 69 g l(‐1) acetic acid in semi‐continuous fermentation. As a final result, average acetic acid productivity has been raised to 0.99 g l(‐1) h(‐1), which was 32% higher than the parental A. pasteurianus. This study is of great significance for decreasing cost of semi‐continuous fermentation for producing high‐strength acetic acid industrially. We envisioned that this strategy will be useful for production of many other desired organic acids, especially those involving cofactor reactions.